Serum Leptin and Ghrelin Levels in Women with Polycystic Ovary Syndrome: Correlation with Anthropometric, Metabolic, and Endocrine Parameters - Shiva Houjeghani (International Journal of Fertility and Sterility, 2012)
Background Polycystic ovary syndrome (PCOS) patients are more prone to abnormal production of some regulatory peptides. In these patients, studies on the serum levels of leptin and ghrelin are controversial. This study aims to investigate serum levels of leptin and ghrelin and their correlation with metabolic and endocrine indices in PCOS. Materials and Methods This case-control study was conducted on 60 women; 30 with PCOS and 30 healthy women whose age and body mass index (BMI) were matched and who were referred to Alzahra Hospital, Tabriz, Iran. Serum levels of leptin, ghrelin, insulin, luteinizing hormone (LH), follicle stimulating hormone (FSH), sex hormone-binding globulin (SHBG), and testosterone were measured. The homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. Descriptive statistics and correlations were performed using SPSS 12.0 for Windows. Results In PCOS women, serum levels of leptin, insulin, HOMA-IR, testosterone, LH, and LH/FSH were significantly higher, while SHBG was lower than in healthy women. Ghrelin and FSH were similar in both groups. Serum levels of leptin correlated with BMI (r=0.85, p < 0.001), waist to hip ratio (WHR) (r=0.55, p < 0.01), insulin levels (r=0.85, p < 0.001) and HOMA-IR (r=0.67, p < 0.01), while ghrelin levels had an inverse association with testosterone (r=-0.32, p=0.04). Conclusion The results showed increased leptin levels while ghrelin remained unchanged in PCOS patients. In PCOS patients, leptin positively correlated with BMI, WHR, insulin, and insulin resistance, while ghrelin was only associated with serum testosterone levels.